Pelatihan Microsoft Excel bagi Guru-guru di SD Negeri 3 Bareng Lor Klaten - Ratna Mustika Dewi; Kurnianingtyas, Chandra Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
SD Negeri 3 Bareng Lor Klaten is an elementary school located in the North Klaten area. Adequate facilities are needed in presenting the right learning facilities for students. The right resources will help in the teaching and learning process in an institution, especially in school units. One of the resources to be aware of is the